The fraction of long-term sickness absence attributable to work environmental factors: prospective results from the Danish Work Environment Cohort Study. Issue 7 (20th June 2007) - Bang Christensen, Karl; Lund, Thomas; Labriola, Merete; Villadsen, Ebbe; Bültmann, Ute
Abstract : Objective: To examine the fraction of long-term sickness absence periods attributable to physical and psychosocial work environmental risk factors. Method: A random population sample was followed for 18 months in a national register of social transfer payments. Mutually adjusted hazard ratios for onset of long-term sickness absence and aetiological fractions were computed. Results: After mutual adjustment, no significant effect of psychosocial work environment factors remained. In men, 23% and 28% of long-term sickness absence were attributable to working mainly standing or squatting, and lifting or carrying loads, respectively. In women, 27% of long-term sickness absence was attributable to bending or twisting of the neck or back. Conclusions: Physical work environment exposures explained between 10% and 30% of long-term sickness absence. The potential for reducing long-term sickness absence is substantial.